The sociology of creativity: PART III: applications – the socio-cultural contexts of the acceptance/rejection of innovations - Burns, T. R.; Corte, U.; Machado, N. (Human Systems Management, 2016)
The three-part article of which this one is Part III is predicated on the principle that creativity is a universal activity, essential in an evolutionary perspective, to adaptation and sustainability. This work on the sociology of creativity has three purposes: (1) to develop the argument that key factors in creative activity are socially based and developed; hence, sociology can contribute significantly to understanding and explaining human creativity; (2) to present a systems approach which enables us to link in a systematic and coherent way the disparate social factors and mechanisms that are involved in creative activity and to describe and explain creativity; (3) to illustrate a sociological systems theory’s (Actor-Systems-Dynamics) conceptualization of multiple interrelated institutional, cultural, and interaction factors and mechanisms and their role in creativity and innovative development with respect to diverse empirical cases. Part I of this article introduced and applied a general model of innovation and creative development stressing the socio-cultural and political embeddedness of agents, either as individuals or groups, in their creative activities and innovative productions. Part II investigated the “context of innovation and discovery” considering a wide range of applications and illustrations. This 3rd segment, Part III, specifies and analyzes the “context of acceptance and institutionalization” where innovations and creative developments are socially accepted , legitimized, and institutionalized or rejected, suppressed. A number of cases and illustrations are considered. Power considerations are part and parcel of these analyses, for instance the role of the state as well as powerful private interests and social movements in facilitating and/or constraining innovations and creative developments in society. In the perspective presented here, generally speaking, creativity can be consistently and systematically considered to a great extent as social, cultural, institutional and material as much as psychological or biological.